Mapping the global research on project-based learning: a bibliometric and network analysis (2014–2024) - Mota, Fabio Batista; Cabral, Bernardo Pereira; Braga, Luiza Amara Maciel; Lopes, Renato Matos (Frontiers in Education, 2025)
BackgroundProject-based learning (PjBL) is a widely adopted educational approach known for fostering critical skills such as collaboration, problem-solving, and self-regulated learning. Despite its global implementation across various educational levels and disciplines, there has been limited comprehensive analysis of global research trends in PjBL.ObjectiveThis study maps the global research on PjBL.MethodsWe used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, bibliometrics, and network analyses to analyze 2,273 peer-reviewed articles indexed in the Web of Science Core Collection and published between January 2014 and August 2024.ResultsOur findings show a significant increase in PjBL research over time, with an 800% growth in publications since 2014. The most frequent keywords are engineering education, higher education, and STEM, and the main research areas are Education and Educational Research, Engineering, and Computer Science. The United States of America, Spain, and China are the leading countries in publications. Additionally, the network analysis shows strong collaborations, particularly between organizations in the USA and Asia.ConclusionThis study offers a broad understanding of the global research landscape on PjBL, delivering key insights for future studies and promoting collaborative research among organizations worldwide.